Dynamics and stability of milling thin walled pocket structure. (1st September 2018) - Ren, Song; Long, Xinhua; Meng, Guang
Abstract: In this paper, the multi pocket structure is regarded as a combination of Kirchhoff plates. A semi analytical solutions for the vibration of this thin walled structure are obtained by the subdomain decomposition method which is proposed by the authors earlier. Thereafter, a dynamic cutting model concerning the cutting position and the vibration states is adopted to modelling the milling force. Both the vibration model and the dynamic cutting model are integrated together to establish the governing equation which fully consider the dynamic features for the thin wall milling process. Based on the quasi static hypothesis, the stability of the milling of thin walled structure can be regarded as the stability of cutting at a series of discrete points. And the semi discretization method is applied to analysis the stability for this thin wall milling process. It is found that the critical depth of cut is appropriately inversely proportional to the square of mode shape for each single mode. In addition, the influence of the multimode and the mode coupling effects on the milling stability are discussed. It gives clearer insight into the dynamics and stability for the milling processes of thin walled structure. Highlights: Formulations are obtained for vibration of thin walled pocket structure. Higher order mode components can dominate the cutting vibration. Milling stability at different cutting locations is analyzed. Mode interaction and frequency modulation are discussed.